(untitled) (Global Journal of Human-Social Science, 2024)
This article aims to discuss the importance of the characters in the book A mulher que escreveu a Bíblia by Moacyr Scliar. The characters analyzed are characterized as being ugly, and one of them has an amputated limb. They are the ugly, unnamed character, and the little shepherd who was beautiful at first. These characters coexist with others who are very beautiful. In this way she recounts her own existence from the time when she was only the daughter of the anonymous leader of a tribe until she became the wife of King Solomon. The aim is to verify how the attitudes of the ugly characters contrasts with the actions of the beautiful characters in the narrative. However ugliness is fundamental so that we can understand the work.